Gene Polymorphisms in the Renin-Angiotensin-Aldosterone System and Breast Carcinogenesis: Is There a Connection? - Loh, Julian Kenrick (Trinity Student Medical Journal, 2008)
Breast cancer is the second most common type of cancer in the world. In this article, studies are considered, which suggest a pattern may exist between polymorphisms in genes of the renin-angiotensin-aldosterone system (RAAS) and the risk of developing breast cancer. Polymorphisms of angiotensin converting enzyme (ACE), angiotensin II receptor type 1 (AGTR1) and angiotensinogen are investigated. The polymorphisms in the ACE gene cause variations in the level of ACE and therefore affect the level of angiontensin II, which is thought to contribute to breast carcinogenesis. Studies into insertion/ deletion (I/D) polymorphisms and the single nucleotide polymorphism (SNP) A-240T show that carriers of the DD genotype of the I/D polymorphism or the TT genotype of the SNP had significantly greater chances of developing breast cancer than carriers of the II or AA genotypes. SNPs in the AGTR1 gene may reduce the risk of breast cancer by either determining the binding efficiency of angiotensin II to the receptor or by interfering with the downstream signaling cascade that is required for angiotensin II to elucidate it’s carcinogenic effect. Studies on the SNPs A-168G, C-535T and T-825A are presented here and it is evident that carriers of the AA genotype, CC genotype and TT genotype may have a higher risk of developing breast cancer than carriers of GG, TT and AA genotypes respectively. A SNP, M-235T, in the angiotensinogen gene also supports the connection of polymorphisms in the RAAS system to breast cancer. This receptor may provide a useful target for pharmacological therapy in patients suffering from breast cancer. In the future polymorphisms in ACE, angiotensin II and AGT may prove to be markers for and long term use of ACE inhibitors may prove to be protective against breast cancer.